2014
DOI: 10.1155/2014/867827
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mortality among Adult HIV-Infected Patients on Antiretroviral Therapy in a Rural Hospital in Southeastern Nigeria: A 5-Year Cohort Study

Abstract: Background. Study examined the determinants of mortality among adult HIV patients in a rural, tertiary hospital in southeastern Nigeria, comparing mortality among various ART regimens. Methods. Retrospective cohort study of 1069 patients on ART between August 2008 and October 2013. Baseline CD4 counts, age, gender, and ART regimen were considered in this study. Kaplan-Meier method was used to estimate survival and Cox proportional hazards models to identify multivariate predictors of mortality. Median follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
7
2
Order By: Relevance
“…The knowledge of these factors responsible for mortality among PLHIV can guide the policy makers to address them, suggesting and implementing remedial measures through the program. The mortality rate in our study cohort was 14.4%, which was higher than in similar studies conducted in Africa [9][10][11], which is probably due to the higher number of deceased patients in WHO stage 3/4 of the disease in our study.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The knowledge of these factors responsible for mortality among PLHIV can guide the policy makers to address them, suggesting and implementing remedial measures through the program. The mortality rate in our study cohort was 14.4%, which was higher than in similar studies conducted in Africa [9][10][11], which is probably due to the higher number of deceased patients in WHO stage 3/4 of the disease in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…Studies from the Sub-Saharan African region have observed a similar trend, with respect to the role of nutrition in PLHIV. Low BMI was associated with mortality in studies from Burkino Faso [9,14], northern Ethiopia [10] and Nigeria [11], where, as in studies from Tanzania [6] and Ethiopia [15], history of significant weight loss, and weight less than 45 kg were predictors of mortality. Poor nutritional status at the initiation of ART and its deterioration within the first 3 months of starting therapy was an important predictor of mortality in another study from Tanzania [16].…”
Section: Discussionmentioning
confidence: 84%
“…The proportion of LTFU of 22.6% seen in this study was lower than 36.6% reported in Cameroon [ 13 ] and 27.6% in South Africa [ 27 ]. It was, however, higher than the 15.5, 17.7, 15.6, 14.5, 19.6, and 21.7% detected in India, Sub-Saharan Africa, Nigeria, Hadiya (Southern-Ethiopia), Ethiopian public hospitals, and in Southern Nations Nationalities and Peoples (SNNP) Region (Ethiopia), respectively [ 11 13 , 28 30 ]. The LTFU in our study turned out to be higher than those of the preceding reports because of travel costs patients had to cover to reach clinics.…”
Section: Main Textmentioning
confidence: 78%
“…The significant risk factors of LTFU are sex, youth, occupation, and lack of formal education [ 11 13 ] as well clinical characteristics, like CD4-count, WHO stage, functional status and Isoniazid Preventive Therapy (IPT) [ 9 , 12 , 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hospital also offers specialist services in surgery, ophthalmology, oncology, internal medicine as well as obstetrics and gynaecology. [ 7 ]…”
Section: Methodsmentioning
confidence: 99%